2001
DOI: 10.1016/s0550-3213(01)00070-0
|View full text |Cite
|
Sign up to set email alerts
|

The Higgs mechanism in non-commutative gauge theories

Abstract: This paper investigates the non-commutative version of the Abelian Higgs model at the one loop level. We find that the BRST invariance of the theory is maintained at this order in perturbation theory, rendering the theory one-loop renormalizable.Upon removing the gauge field from the theory we also obtain a consistent continuum renormalization of the broken O(2) linear sigma model, contradicting results found in the literature. The beta functions for the various couplings of the gauged U(1) theory are presente… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0
3

Year Published

2001
2001
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(19 citation statements)
references
References 26 publications
(29 reference statements)
1
15
0
3
Order By: Relevance
“…It has also been argued that spontaneously broken noncommutative gauge theories are renormalizable (Petriello, 2001).…”
Section: Gauge Theoriesmentioning
confidence: 99%
“…It has also been argued that spontaneously broken noncommutative gauge theories are renormalizable (Petriello, 2001).…”
Section: Gauge Theoriesmentioning
confidence: 99%
“…Let us remind that in ordinary gauge theories at zero temperature, the poles of propagators are gauge invariant quantities [26]. In non-commutative gauge theories, there is no general proof of this statement, but only checks at one-loop order [5] [27] 3 .…”
Section: Vector Quasi-particles and Tachyonsmentioning
confidence: 99%
“…Other investigations regarding different non-commutative models were done in [28,29,30,31]. Within these models it was found that the situation for the Goldstone theorem, followed rather closely the features of the commutative case.…”
Section: Introductionmentioning
confidence: 96%